ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISTEM PERSAMAAN LINEAR DUA VARIABEL SISWA KELAS VIII SMP KRISTEN GPID SUMBERSARI DITINJAU DARI GAYA KOGNITIF : Analysis of Problem Solving Ability The Two Variable Linear Aquation System at The Eighth Grade Students of Gpid Sumbersari Christian Junior High School in Terms of Cognitive Style - Rusmawa, I Ketut Beni; Sugita, Gandung; Anggraini, Anggraini; Murdiana, I Nyoman (Aksioma, 2025)
This research is a descriptive study that uses a qualitative approach aims to obtain a description of the problem solving ability of two variable linear aquation system of grade VIII students of GPID Sumbersari Christian Junior High School in terms of cognitive style based on Polya's steps. Subjects in this study consisted of 4 students, namely subject FIt (selected students who are FI cognitive style from the GEFT test results which fall into the high FI category), Subject FIs (selected students who are FI cognitive style from the GEFT test results which fall into the medium FI category), FDs (selected students who are FD cognitive style from the GEFT test results which fall into the medium FD category) and subject FDr (selected students who are FD cognitive style from the GEFT test results which fall into the low FD category). The instruments in this study are GEFT test, problem solving ability test of two variable linear aquation system, and interview guidelines. The results showed that the problem solving ability of FI cognitive style subjects is better than FD cognitive style subjects. Where, the problem solving ability of two variable linear equation system of FI cognitive style subject that is FIt subject has been in accordance with the four stages of Polya by giving the correct conclusion and FIs subject has also been in accordance with the stage of understanding the problem and planning problem solving however, there is a calculation error at the stage of implementing the problem solving plan and at the stage of re-examining the answer the conclusion obtained is wrong. Meanwhile, the problem solving ability of the two variable linear equation system of FD cognitive style subjects, namely FDs and FDr subjects even though they are in accordance with the stage of understanding the problem, and planning problem solving. However, at the stage of performing the problem solving plan is incomplete and at the stage of checking the answer the conclusion obtained is wrong.